"MY BUNCEE" : A WEB-BASED PRESENTATION TOOL TO IMPROVE ET-12 STUDENTSâ€™ MOTIVATION,ENGAGEMENT, AND ACHIEVEMENT - Diana Luspa (Esteem Journal of English Education Study Programme, 2020)
The Comet Series of textbooks for the Intermediate levels of LB LIAâ€™s English for Teens Program is prepared to suit the needs of students between thirteen and fifteen years of age. Despite this psychological breakthrough stage, students of ET-12 encountered some problems in understanding the value of the task to them, especially when they did the presentation task. It was found that they were less motivated and engaged to do it, and it influenced their achievement. In line with the principles behind the course , motivation and confidence, fun but more serious and insightful tasks are definitely things that the students need in order that the objectives of the teaching and learning are successfully achieved. To address the issues, Buncee application,Â  a web-based presentation tool,was used to improve these studentsâ€™ motivation and engagement. Â How â€œBunceeâ€ helpedthe students to achieve the goal was Â conducted in eight meetings. The process was recorded using observation, journal, and questionaires and the data was analyzed by using SPSS.Â  The results showed that the Buncee was as an effective tool to improve studentsâ€™ motivation and engagement. Gen Z is accustomed to personalize everything by choosing what they want (and just as important, what the donâ€™t want). These attitudes will inevitably influence education. Therefore,teachers need to adapt their pedagogical approaches.Keywords: Buncee, Motivation, Engagement, Achievement